2012
DOI: 10.1088/2041-8205/750/1/l12
|View full text |Cite
|
Sign up to set email alerts
|

NO ICE HYDROGENATION: A SOLID PATHWAY TO NH 2 OH FORMATION IN SPACE

Abstract: Icy dust grains in space act as catalytic surfaces onto which complex molecules form. These molecules are synthesized through exothermic reactions from precursor radicals and, mostly, hydrogen atom additions. Among the resulting products are species of biological relevance, such as hydroxylamine-NH 2 OH-a precursor molecule in the formation of amino acids. In this Letter, laboratory experiments are described that demonstrate NH 2 OH formation in interstellar ice analogs for astronomically relevant temperatures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
79
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(86 citation statements)
references
References 31 publications
6
79
1
Order By: Relevance
“…(3) The final products of NO 2 hydrogenation are NH 2 OH and H 2 O. Hydroxylamine is found to be formed through a series of barrierless surface reactions as previously shown by Congiu et al 11,12 and Fedoseev et al 13 Both water and hydroxylamine are important molecules for the formation of COMs in space (Part II). (6) Surface coverage (submonolayer and multilayer regimes) has a small but noticeable impact on the final products.…”
Section: Conclusion (Parts I and Ii)mentioning
confidence: 83%
See 1 more Smart Citation
“…(3) The final products of NO 2 hydrogenation are NH 2 OH and H 2 O. Hydroxylamine is found to be formed through a series of barrierless surface reactions as previously shown by Congiu et al 11,12 and Fedoseev et al 13 Both water and hydroxylamine are important molecules for the formation of COMs in space (Part II). (6) Surface coverage (submonolayer and multilayer regimes) has a small but noticeable impact on the final products.…”
Section: Conclusion (Parts I and Ii)mentioning
confidence: 83%
“…63,64 NO ice can be hydrogenated in a barrierless way to form solid hydroxylamine. [11][12][13] The NO that reacts with the oxygen allotropes in the solid phase will form efficiently NO 2 . The nitrogenation of NO will lead to the destruction of NO and the formation of N 2 .…”
Section: Astrophysical Implicationsmentioning
confidence: 99%
“…The experiments were performed using the FORMOLISM setup (Amiaud et al 2006;Congiu et al 2012). In an ultra-high vacuum chamber a gold mirror covered with amorphous silicates, oxidized graphite, or compact amorphous water substrate was held at very low temperatures (∼10 K).…”
Section: Methodsmentioning
confidence: 99%
“…This prediction of chemical models has recently been confirmed by laboratory experiments of NO hydrogenation that demonstrated the destruction of NO and the formation of HNO, N 2 O and NH 2 OH (Congiu et al 2012). These authors showed that if hydrogenation dominates, NO is rapidly destroyed and NH 3 , N 2 O and NH 2 OH are the most abundant N-bearing species (see Fig.…”
Section: Ices In Dense Cloudsmentioning
confidence: 52%